Effects of weed management on phytoseiid populations in vineyards of Lombardy (ltaly) (Bollettino di zoologia agraria e bachicoltura, 2024)
The role of weeds present in the vineyards as refuges for phytoseiid mites and the impact of cultura! practices on the floristic composition and on the population of mites was investigated. The experiment was carried out in two vineyards ofLombardy, one was abandoned and the other was cultivated normally. The structure of the herbaceous community was defined. The observations on the mite fauna were carried out by collecting samples of leaves of the most common plant species. The vegetation was much more complex in the abandoned vineyard. Even the composition in the abandoned field was influenced by a greater presence of Dicotyledons, both in number of species and in abundance. The vegetation cover was much greater in conditions of naturalness than on the cultivated field. The phytoseiids were abundant in the abandoned vineyard, and they were even absent on the grass in the other field. In semi-natural conditions five species were collected. Phytoseiids were never found on Monocotyledons. The investigations show the great ecological importance of the herbaceous cover for the upkeep of the phytoseiid populations, for which it is possible to hypothesise a flow from and towards the cultivation. Nevertheleess, the remarkable negative influence of the common cultural practices seemed just as evident on the floristic composition as on the phytoseiids.
Keywords: green cover; cultural practices; Phytoseiids; ecological refuge; floristic composition; biodiversity